2017
DOI: 10.1186/s12886-017-0448-9
|View full text |Cite
|
Sign up to set email alerts
|

Damage to the macula associated with LED-derived blue laser exposure: A case report

Abstract: BackgroundLight emitting diodes laser is emerging as an important source of light replacing conventional lights. It is widely used for illumination in the bar where young people love to go. But not everyone knows about the light damage to the eye especially to the macula. In this article, we report the case of a macular damage induced by LED-derived blue laser in a bar, studied with optical coherence tomography (OCT) to evaluate the retinal lesion and multifocal electroretinography (mfERG) to evaluate function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…One study that began the regime at 1 mg/kg/day found improvement compared with patients who did not receive treatment [7]. Another treatment reported as beneficial in some studies is lutein 20 mg/day for at least one month, administered for its antioxidant and anti-inflammatory effects along with its known protection in other macular diseases [9,13,14]. In this case, lutein was started at the one-week follow-up in addition to corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…One study that began the regime at 1 mg/kg/day found improvement compared with patients who did not receive treatment [7]. Another treatment reported as beneficial in some studies is lutein 20 mg/day for at least one month, administered for its antioxidant and anti-inflammatory effects along with its known protection in other macular diseases [9,13,14]. In this case, lutein was started at the one-week follow-up in addition to corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Another treatment, which some reports have shown is beneficial, is lutein 20mg daily for at least one month, administered for its antioxidant and anti-inflammatory effect plus known protection in other macular diseases [9,13,14]. In this case lutein was started at one week follow up in addition to corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Dark lenses cause mydriasis and, as a result, allow more radiation to enter the eye. Commercially available, high quality lenses which filter out wavelengths most hazardous to the eye, particularly those below 450 nm, should instead be used 1, 11, 12. However, protective eyewear may interfere with proper viewing of the aircraft and/or controller.…”
Section: Discussionmentioning
confidence: 99%